The Emerald handbook of luxury management for hospitality and tourism - Kotur, Anupama S.; Dixit, Saurabh Kumar (Emerald Publishing Limited, 2022)
Luxury is an ever-evolving concept with various interpretations in the domain of hospitality and tourism. The understanding of luxury hospitality and travel has revolved around exclusive and authentic experiences, nuanced by finer things with a focus on value rather than price. The marketing of luxury products and services has become increasingly complex as these products and services are associated not only with an image of quality, performance, and authenticity but also with how extreme experiences and products fulfil the lifestyle constructs of consumers. The Emerald Handbook of Luxury Management for Hospitality and Tourism brings together global philosophies, principles and practices in luxury tourism management from both supply and demand perspectives. Several global case studies are presented, further illustrating the changing paradigms of luxury travel market and consumers enabling insight into the upcoming global luxury travel market. Encompassing the vibrant case studies and contemporary discussions on luxury hospitality and tourism developments during the post-pandemic era, this volume will serve as an essential resource for students, researchers, and industry practitioners of hospitality, tourism, management, and marketing consumer behavior, and consumer studies.